A lifetime of communication : transformations through relational dialogues - Yingling, Julie (LEA's series on personal relationships., 2004)
Julie Yingling considers communication and relationships through the lens of human development. Beginning with infancy and moving through adolescence to adulthood, the chapters examine communication and cognition in the various stages of human development.